1983
DOI: 10.1159/000234855
|View full text |Cite
|
Sign up to set email alerts
|

New Preparative Schedule and Further Characterization of a Thymocyte Specific Growth Factor from Calf Thymus

Abstract: Purification of a thymocyte specific growth factor is described. A formic acid extract of calf thymus was acetone precipitated, extracted with acidic methanol and precipitated with ether. With an assay based on the stimulation of DNA synthesis in thymocyte cultures the crude extract was purified by several steps of gel filtration and ion exchange chromatography. The stimulating activity had an apparent Mr of 1,600 and a pI of 5.6–5.9 and was devoid of reactive amino groups. It behaved amphoteric and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1983
1983
1990
1990

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The purification schedule has recently been published in detail [6). An extract was prepared from pooled calf thymuses by sequen tial steps of solvent extractions and precipitations.…”
Section: Preparation O F Thymic Growth Factormentioning
confidence: 99%
See 1 more Smart Citation
“…The purification schedule has recently been published in detail [6). An extract was prepared from pooled calf thymuses by sequen tial steps of solvent extractions and precipitations.…”
Section: Preparation O F Thymic Growth Factormentioning
confidence: 99%
“…In previous papers, we have reported on the biochemical and functional properties of a thymic factor with ability to induce DNA synthesis specifically in immunologically in competent immature thymocytes [3][4][5]. The factor was shown to be biochemically and functionally distinct from other lymphocyte growth factors and from thymic differentiation hormones [6,7]. Kinetic studies showed that the thymic factor stimulated DNA syn thesis with a peak effect 4-8 h after start of culture [4,5], indicating that the target cells were Gl thymocytes which were influenced to initiate DNA synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Calf thymus extract was prepared and purified as described in a previous paper [9). The purified active material from the Bio-Gel P-4 column was used in an amount resulting in maximal stimula tion of DN A synthesis in thymcocytes.…”
Section: Preparation O F Thymocyte Specific Growth Factormentioning
confidence: 99%
“…Crude extract [9] was prepared from 20 g of each guinea pig tissue and calf thymus and separated on Sephadex G 50 fine. Fractions were pooled, lyophilized and subjected to Bio-Gel P-4 chromatog raphy.…”
Section: Preparation O F Different Tissue Extractsmentioning
confidence: 99%
See 1 more Smart Citation